MERITS AND DRAWBACKS OF ONLINE AND OFFLINE LESSONS IN UZBEKISTAN - Turdaliyeva Komila (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
This article examines the benefits and drawbacks of both online and offline learning environments, especially in light of recent educational reforms. Although online courses provide accessibility, flexibility, and individual pace they can also result in unequal access, a lack of self-discipline, and loneliness. On the other hand, offline (traditional) education provides structure, face-to-face communication and social growth, but it might not be as flexible or integrate technology. A balanced and blended approach that incorporates the two modes may offer the most effective learning environment. Based on recent research and practical observations, the article offers insights for educators, students, and policymakers.